The internationalization case of Yunit consulting, LDA.: in-depth country analysis - Spain - Mendes, Ricardo Gadit (2022)
Yunit Consulting is a Portuguese management consulting company wishing to expand its business. This report, presenting an extensive internationalization plan, incorporates a firm overview, an industry assessment, a country clustering, and a ranking analysis. Having identified five potential target markets, Spain is then thoroughly assessed through a PESTEL analysis, a forecast of the industry and company’s sales potential, and the evaluation of the market entry conditions. Further, a strategic alliance with a digital transformation consulting company in Catalunya was found suitable. Thus, a marketing strategy was developed, together with a financial assess the viability of such international expansion.